Developing a risk management approach based on reinforcement training in the formation of an investment portfolio - Martovytskyi, Vitalii; Argunov, Volodymyr; Ruban, Igor; Romanenkov, Yuri (Eastern-European Journal of Enterprise Technologies, 2023)
Investments play a significant role in the functioning and development of the economy. Risk management is an integral part of the formation of the investment portfolio. This means that an investor must be willing to take on a certain level of risk in order to receive a certain level of return. However, when forming an investment portfolio, an investor faces such problems as market unpredictability, asset correlation, incorrect asset allocation. Therefore, when forming an investment portfolio, an investor should carefully study all possible risks and try to minimize them. The object of research is an approach to risk management in the formation of an investment portfolio using the method of reinforcement training. The basic principles of formation of the investment portfolio and determination of risks are described. The application of the method of reinforcement training for building a model of risk management of investment portfolio is considered. The process of selecting optimal investment assets based on alternative data sources that minimize risks and maximize profits is also considered. A functional model of the process of risk optimization in the formation of an investment portfolio based on machine learning methods has been developed. The functional model constructed makes it possible to build a process of risk optimization, including asset selection, risk comparison and assessment, to form an investment portfolio and monitor its risks. The study results showed that the proposed approach to the formation of the investment portfolio increased the total growth of the investment portfolio by 0.4363 compared to the base model. Also, the volatility indicator improved compared to the market, as evidenced by the percentage difference between the initial and final cash amount, which increased from 128.98 to 295.57